2017
DOI: 10.1007/s11892-017-0891-2
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Advanced Glycation End Products and Cardiometabolic Risk

Abstract: Clinical studies in subjects with diabetes mellitus have shown that high intake of dietary AGEs increases inflammation markers, oxidative stress, and could impair endothelial function. In subjects at risk for cardiometabolic diseases (with overweight, obesity, or prediabetes), dietary AGE restriction decreases some inflammatory molecules and improves insulin sensitivity. However, studies in healthy subjects are limited, and not all of the studies have shown a decrease in circulating AGEs. Therefore, it is stil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
55
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 102 publications
0
55
0
Order By: Relevance
“…Regardless of the presence or absence of DM, peak VO 2 levels were significantly lower in the high SAF group than in the low SAF group. SAF, skin autofluorescence; DM, diabetes mellitus been observed to be associated with aging, lifestyle habits such as specific food intake, and smoking, in addition to the presence of chronic inflammatory conditions such as metabolic syndrome, arteriosclerosis, and renal disease [9,10,43]. The deterioration of EC with AGE accumulation may, therefore, be the result of AGEs causing the functional decline of several organ systems that regulate EC, regardless of DM status.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the presence or absence of DM, peak VO 2 levels were significantly lower in the high SAF group than in the low SAF group. SAF, skin autofluorescence; DM, diabetes mellitus been observed to be associated with aging, lifestyle habits such as specific food intake, and smoking, in addition to the presence of chronic inflammatory conditions such as metabolic syndrome, arteriosclerosis, and renal disease [9,10,43]. The deterioration of EC with AGE accumulation may, therefore, be the result of AGEs causing the functional decline of several organ systems that regulate EC, regardless of DM status.…”
Section: Discussionmentioning
confidence: 99%
“…3 TDSCs can promote tendon repair and regeneration, and maintain tendon homeostasis. 7,8 Meanwhile, studies showed that AGEs can accumulate in long-lived tissues like tendons and bridge between the free amino groups of neighbouring proteins to form intermolecular crosslinks, which in turn increases tissue stiffness and brittleness. 5 Advanced glycation end products (AGEs), kinds of oxidative derivatives resulting from diabetic hyperglycaemia, are known to contribute to the complications of DM by raising intracellular oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…6 Extracellular AGEs induce cellular oxidative stress, inflammation and apoptosis in DM complications such as cardiovascular disease and chronic kidney disease. 7,8 Meanwhile, studies showed that AGEs can accumulate in long-lived tissues like tendons and bridge between the free amino groups of neighbouring proteins to form intermolecular crosslinks, which in turn increases tissue stiffness and brittleness. 9 Pioglitazone (Pio), a peroxisome proliferator-activated receptor (PPAR) γ agonist, is widely used in clinical practice to treat type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…As the last step, through several reactions including dehydration, cyclization, fragmentation, and oxidation, the irreversible compounds known as AGEs are formed. [24] Although AGEs are a complex group of compounds there are specific AGEs that have a better correlation with some diabetic complications, among them, pentosidine, a fluorescent AGE formed with lysine and arginine, first described by Sell and Monnier [25], has been related to diabetic nephropathy [26], particularly free pentosidine in urine (uPen) has been determined as a marker of progression rate [27,28]. Besides, pentosidine has been associated with low estimated GFR in non proteinuric type 2 diabetic patients, issue that highlights pentosidine determination potential as CKD progression marker even in early stages [29].…”
Section: Introductionmentioning
confidence: 99%